Dampak Layanan Infrastruktur Digital Terhadap Efektivitas Pembelajaran: Bukti Dari Sekolah Menengah Pertama Di Pematangsiantar - Grace Angel Florense Purba Siboro; Nova Evelin Saragih; Dewani Oktobeni Sidabutar; Juli Herawati Padang; Widya Vani Sitepu; Mika Debora Napitupulu; Sarni Pebrianti Manurung; Ady Frenly Simanullang (Young Journal of Social Sciences and Humanities, 2026)
This study explores the impact of digital technology on the effectiveness of the teaching and learning process through an examination of infrastructure services in a secondary school. For this purpose, field observations and a literature review were employed. The main findings indicate that the available digital technology infrastructure—including hardware (45 computer/laptop units with a 1:3 ratio, projectors in 36% of classrooms, and 60% of students owning personal devices), internet network (50 Mbps Wi-Fi covering 40% of classrooms), free digital platforms (Google Classroom, YouTube Edu, e-books, and simulations), as well as technical support (2 IT staff, maintenance every 6 months, official policies, and teacher training twice a year)—has supported positive outcomes in learning digitalization efforts. Descriptive and theoretical analysis shows that digitalization initiatives yield positive impacts, including enhanced accessibility, interactivity, motivation, and learning outcomes. However, potential negative impacts exist, such as digital divides, distractions, and unequal access due to suboptimal infrastructure. The study's conclusion emphasizes the importance of digital infrastructure service capacity and user readiness as key success factors. Recommendations include equitable infrastructure development (improving network coverage and device availability), additional technical resources, and ongoing teacher training to optimize the effectiveness and efficiency of teaching and learning in school environments.